RANCANG BANGUN SISTEM JUAL BELI ALAT SEKOLAH DI KOPERASI SEKOLAH SDN 2 BERKOH DENGAN METODE WATERFALL - Sulistiyasni, Sulistiyasni; Setianti, Novita; Sopacua, Grace Maria Natasya (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2024)
In the current digital era, the application of technology has become a key element in improving efficiency and service quality, including in the operation of school cooperatives. Technology facilitates the management of the sale of school supplies in a more structured and efficient manner. School cooperatives, which serve as providers of students' needs, require a digital system to ensure that inventory and transactions can be managed optimally. This study aims to design and implement a web-based school supplies sales system at SDN 2 Berkoh's cooperative using the Waterfall method, to improve the cooperative's operational efficiency. This research utilizes the Waterfall method, covering the stages of requirement analysis, system design, implementation, and testing. System testing is conducted using the Blackbox approach to ensure that all features, such as inventory and transaction management, function according to the specifications. Additionally, system usability testing uses the System Usability Scale (SUS), involving 11 respondents to assess the ease of system use. The Blackbox testing results show that the system functions well in all main features, such as transaction recording and stock management. The SUS testing produced a score of 77, indicating that the system is quite easy to use. With this system in place, it is expected that the school cooperative can operate more efficiently, enabling students to meet their school needs more quickly and in an organized manner. Keywords: Buying and Selling System, School Cooperative, Waterfall, Black Box Testing, System Usability Scale